Atorvastatin Promotes Macrocalcification, But Not Microcalcification in Atherosclerotic Rabbits: An 18F-NaF PET/CT Study. Issue 4 (October 2021) - Zhang, Xuehui; Chen, Xue; Liang, Zhe; Nie, Maoxiao; Yan, Yunfeng; Zhao, Quanming
Abstract : Introduction: Our study aimed to investigate the effect of atorvastatin on plaque calcification by matching the results obtained by 18 F-sodium fluoride ( 18 F-NaF) positron emission tomography (PET)/computed tomography (CT) with data from histologic sections. Methods and Results: The rabbits were divided into 2 groups as follows: an atherosclerosis group (n = 10) and an atorvastatin group (n = 10). All rabbits underwent an abdominal aortic operation and were fed a high-fat diet to induce atherosclerosis. Plasma samples were used to analyze serum inflammation markers and blood lipid levels. 18 F-NaF PET/CT scans were performed twice. The plaque area, macrophage number and calcification were measured, and the data from the pathological sections were matched with the 18 F-NaF PET/CT scan results. The mean standardized uptake value (0.725 ± 0.126 vs. 0.603 ± 0.071, P < 0.001) and maximum standardized uptake value (1.024 ± 0.116 vs. 0.854 ± 0.091, P < 0.001) significantly increased in the atherosclerosis group, but only slightly increased in the atorvastatin group (0.616 ± 0.103 vs. 0.613 ± 0.094, P = 0.384; 0.853 ± 0.099 vs.0.837 ± 0.089, P < 0.001, respectively). The total calcium density was significantly increased in rabbits treated with atorvastatin compared with rabbits not treated with atorvastatin (1.64 ± 0.90 vs. 0.49 ± 0.35, P < 0.001), but the microcalcification level was significantly lower. There were more microcalcification deposits in the areas with increased radioactive uptake of 18 F-NaF. Conclusions: Our study suggests that the anti-inflammatory activity of atorvastatin may promote macrocalcification but not microcalcification within atherosclerotic plaques. 18 F-NaF PET/CT can detect plaque microcalcifications.